2016
DOI: 10.1001/jama.2016.8882
|View full text |Cite|
|
Sign up to set email alerts
|

Primary Care Interventions to Support Breastfeeding

Abstract: IMPORTANCE Although 80% of infants in the United States start breastfeeding, only 22% are exclusively breastfed up to around 6 months as recommended by a number of professional organizations. OBJECTIVE To systematically review the evidence on the benefits and harms of breastfeeding interventions to support the US Preventive Services Task Force in updating its 2008 recommendation. DATA SOURCES MEDLINE, PubMed, Cumulative Index for Nursing and Allied Health Literature, Cochrane Central Register of Controlled Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 81 publications
1
55
0
3
Order By: Relevance
“…A possible preventive effect of a longer duration of breastfeeding is sometimes cited in reviews of the evidence for breastfeeding recommendations (8,9). This can lead to a sense of guilt among mothers of children who develop type 1 diabetes, if the mother did not fully comply with the recommendations for duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible preventive effect of a longer duration of breastfeeding is sometimes cited in reviews of the evidence for breastfeeding recommendations (8,9). This can lead to a sense of guilt among mothers of children who develop type 1 diabetes, if the mother did not fully comply with the recommendations for duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding has been associated with a number of positive health outcomes, and a possible protective effect against type 1 diabetes in children has been cited as evidence for the importance of breastfeeding (8,9). Previous systematic reviews and meta-analyses of observational studies have suggested that breastfeeding more than 3 months (10,11), and exclusive breastfeeding for more than 2 weeks (12), are associated with an approximately 15–30% lower risk of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the postpartum period is a key inter-conception phase with implications for preconception health and care [51]. While the areas of breastfeeding, postnatal depression and sleep are well studied on their own [52][53][54], further investigation into how we can address and implement these and other modifiable factors to promote healthy lifestyles, and therefore optimise weight status, for women between and in future pregnancies is warranted. As with antenatal interventions, understanding the key effective components of interventions to reduce postpartum weight retention, alongside vital implementation research focused on overcoming barriers to postpartum self-care and healthy lifestyle, are vital [55].…”
Section: Discussionmentioning
confidence: 99%
“…Existence of activities to support multilevel breastfeeding backed and framed within specific policies increases the impact on exclusive breastfeeding rates and on its duration. (25) Although in recent decades many efforts have been invested to better understand the effectiveness of different support interventions for breastfeeding; (5,25) few studies have focused on understanding relational, organizational, and contextual aspects that could impact upon this practice and, thereby, on the care required to support it. (26) The results herein contribute to understanding how the context could influence positively or negatively on the results of interventions implemented to support breastfeeding.…”
Section: Discussionmentioning
confidence: 99%